2021
DOI: 10.4103/ijabmr.ijabmr_46_20
|View full text |Cite
|
Sign up to set email alerts
|

Client satisfaction of antiretroviral therapy service delivery: A cross-sectional study at an antiretroviral therapy center

Abstract: Context: People living with HIV (PLHIV)/AIDS are faced with the task of maintaining optimal health status despite an increasing insult to their immune status. Antiretroviral therapy (ART) centers provide comprehensive services to all PLHIV enrolled under the program. Patients with higher satisfaction levels may also have improved health outcomes. Aim: The aim of this study was to assess the client's satisfaction on ART service delivery and to identify the factors associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Clients identified appointment wait times, stigma, confidentiality and VL services (specifically long turnaround times [TAT]) as the highest priority issues to be addressed at these facilities, which align with service delivery aspects that tend to be predictors of client satisfaction [ 16 , 17 , 18 ]. Additional recommendations included more flexible physical access to facility compounds and more welcoming waiting rooms.…”
Section: Resultsmentioning
confidence: 99%
“…Clients identified appointment wait times, stigma, confidentiality and VL services (specifically long turnaround times [TAT]) as the highest priority issues to be addressed at these facilities, which align with service delivery aspects that tend to be predictors of client satisfaction [ 16 , 17 , 18 ]. Additional recommendations included more flexible physical access to facility compounds and more welcoming waiting rooms.…”
Section: Resultsmentioning
confidence: 99%
“…articles are eight research articles (Tran et al, 2019); (Tawiye et al, 2021); (Somi et al, 2021); (Adissu et al, 2020); (Atsebeha & Chercos, 2018); (Wung et al, 2016); (Nikitha & Sushant, 2021); (Molas et al, 2022) with the results that most of them were satisfied with the services received but in the study (Abebe et al, 2016) this did not match the results of this study because (Atsebeha & Chercos, 2018;Tran et al, 2019;Adissu et al, 2020;Mekonnen et al, 2021;Nikitha & Sushant, 2021;Tawiye et al, 2021;Sekandi et al, 2023). The results of the analysis of research articles from Atsebeha and Chercos (2018)…”
Section: Arv Treatment Servicesmentioning
confidence: 99%
“…explain that the age group of 36-45 years is more likely to feel satisfied than the age group of 18-25 years, similar to the results of research byAdissu et al, (2020);Tawiye et al, (2021);Sekandi et al, (2023) who also explained that patients over 35 years of age were associated with increased satisfaction with antiretroviral treatment services. Younger patients are impatient and expect more information about their condition and prognosis(Nikitha & Sushant, 2021).Older patients are generally more open, and older patients have lower demands and expectations, so they feel satisfied more quickly(Arifin et al, 2019). According to researchers, age is related to service satisfaction because differences in perspective and acceptance of service at age are influenced by emotion.The research results(Nikitha & Sushant, 2021) found a relationship between education level and satisfaction with ARV treatment services.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Authors collected data between 1988 (27) and 2019 (28), and published it between 1993 and 2021. According to the WHO region, 42 articles were published in Africa (19,22,23,, 9 studies in the South-East Asia (18,(67)(68)(69)(70)(71)(72)(73)(74), 9 studies in the America (7,27,(75)(76)(77)(78)(79)(80)(81), 4 in the Western Pacific (20,(82)(83)(84) and 2 in the European (21,85) region. Specific to country, 17 were from Ethiopia, 12 from Nigeria, 7 from India, 6 each from South Africa and the United States of America, 3 from Tanzania, 2 each from Brazil, Vietnam and Zambia, and 1 each from United Kingdom and Kenya, Australia, Cameroon, Canada, China, France, Kenya, Russia, and Thailand.…”
Section: Characteristics Of Articlesmentioning
confidence: 99%